Increasing Unconfined Compressive Strength of Soft Clay Stabilized with Coir Fiber and Bagasse Ash Mix - Widianti, Anita; Sundi, Svastika Ariana; Rahmawati, Anita; Wibowo, Dian Eksana (UKaRsT, 2024)
Increasing coir fiber and bagasse ash waste can cause environmental degradation. Utilization of this waste in construction work is still rarely done. Coir fiber is a natural material with the highest coefficient of friction and tensile strength. Bagasse ash has a high silica content and is suitable for use as pozzolan. Soil stabilization with a combination of both is expected to improve the geotechnical properties of soft soil. This research aims to analyze the unconfined compressive strength (UCS) and secant modulus of soft clay stabilized with coir fiber-bagasse ash mix. Coir fiber as much as 0.75% and ash with varying contents: 0%, 2%, 4%, 6%, 8%, and 10% of the total weight of the mixture. The specimens were cured for 28 days. UCS tests were conducted according to ASTM D2166-16 with the axial stress and strain relationship curve results to determine the UCS and secant modulus. The results showed that the UCS value and secant modulus value increased along with increasing bagasse ash content. The maximum value was achieved at 8% ash variation with a UCS value of 472.45 kPa (an increase of 382% from a soil-coir fiber mix) and a secant modulus value of 21.94 MPa (an increase of 571% from a mixture of soil and coir fiber). The research results show that this mixed soil is classified as hard soil, which can withstand high loads. It is hoped that the results of this research can become a reference for stabilizing soft soil in the field.